Hormonal and metabolic characteristic of androgen deficiency and its correction by testosterone in men with type 1 diabetes mellitusundergoing programmed hemodialysis - Alexander Evgen'evich Lepetukhin (Endocrinology Research Centre, 2010)
Aim. To study the prevalence of androgen deficiency in men with type 1 diabetes mellitus (DM1) undergoing programmed hemodialysis (PHD) andto develop methods for the treatment of metabolic disorders. Materials and methods. The study included 43 men with DM1 on PHD. Group 1 comprised 20 patients below 40 years of age, group 2 included23 older patients. Patients of group 1 were allocated to subgroup A (treated with testosterone and ether mixture (TEM)); and control subgroup B(n=14 and 6 respectively). Patients of group 2 were divided into subgroup C (treated with TEM) and control subgroup D (n=14 and 9 respectively).Patients in the study and control subgroups were matched for age, duration of DM1, hemodialysis (years), total testosterone (TT, nmol/l), hemoglobin(Hb, g/l) and glycated hemoglobin (HbA1c, %) levels. All the patients were treated with epoetin-beta (EPO-b) on an individual basis depending onHb level; TEM was given thrice weekly. Results. Group 1: age 34.0?3.9 yr, HbA1c 9.3?1.4%, Hb 118.1?9.6 g/l, TT 21.2?6.6 nmol/l. Group 1: age 47.3?3.5 yr, HbA1c 9.5?1.8%,Hb 94.9?5.7 g/l, TT 9.8?3.9 nmol/l. Androgen deficiency was diagnosed in 48.8% (total group), 5.0% (group 1) and 86.9% (group 2) of the patients.Reduction of TT level was not accompanied by a significant rise in LH concentration to above normal values (p>0.05). HbA1c level in eithergroup did not significantly change within 6 months after the onset of the study. Combined treatment with EPO-b and TEM resulted in a Hb concentrationof 118.2?6.7 g/l in subgroup A (p=0.79). Hb level in subgroup C increased to 113.5?6.3 g/l (p=0.009). Hb changes in control groups wereinsignificant. Requirement for EPO-b in subgroups A and C decreased by 32.1% (p=0.007) and 41.1% (p=0.001) respectively but remained unalteredin both control subgroups. Conclusion. Reduction of the TT level in men with DM1 on PHD is a function of age and constitutes an independent risk factor of anemia. Androgendeficiency and its correction have no effect on carbohydrate metabolism. Combined treatment with EPO-b and TEM increases blood Hb level in oldermen and reduces requirement for EPO-b regardless of the age.